2021
DOI: 10.1186/s12917-021-02901-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (VDR) expression in different molecular subtypes of canine mammary carcinoma

Abstract: Background The molecular-based classification of canine mammary carcinomas (CMCs) has been the focus of much current research. Both in canines and humans, the triple-negative (TN) molecular subtype of mammary cancer is defined by a lack of expression of progesterone receptor (PR), oestrogen receptor (ER) and HER2. It has a poor prognosis; no effective targeted therapy is available. Vitamin D displays anticarcinogenic properties, and the expression of its receptor (VDR) has been found in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…The primary aim of this study was to compare serum 25(OH)D concentrations between dogs with TVT and healthy dogs. As has been found in dogs with other cancers (Davies et al, 2012;Nascimento-hama et al, 2022;Russell et al, 2010;Sánchez-Céspedes et al, 2021;, the results demonstrated that serum 25(OH)D concentrations were significantly lower in dogs with TVT than in healthy dogs.…”
Section: Discussionsupporting
confidence: 80%
“…The primary aim of this study was to compare serum 25(OH)D concentrations between dogs with TVT and healthy dogs. As has been found in dogs with other cancers (Davies et al, 2012;Nascimento-hama et al, 2022;Russell et al, 2010;Sánchez-Céspedes et al, 2021;, the results demonstrated that serum 25(OH)D concentrations were significantly lower in dogs with TVT than in healthy dogs.…”
Section: Discussionsupporting
confidence: 80%
“…The histological diagnosis was confirmed on hematoxylin and eosin (H&E)-stained full-sections by two independent pathologists (YMR and RSC) according to Zapulli et al ( 27 ). In addition, assessment of tumor inflammatory cell infiltration and presence of necrosis within the tumor (yes/no) was performed on H&E-stained full sections ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…For molecular classification of canine mammary carcinomas (CMC), the classification previously described by Sánchez-Céspedes et al ( 28 ) was used. Immunostaining of anti-HER2, -PR, -ER, -CK5, -CK14, and Ki67 were semi-quantitatively analyzed based on the intensity and percentage of positive tumor cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations